The Principal's Role in Improving Teacher Professionalism at Madrasah Ibtidaiyah Negeri - Ari Mariani; Deri Wanto; Murni Yanto (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2022)
This study aims to present or find a description of the principal's role in improving teachers' professionalism at Madrasah Ibtidaiyah Negeri (MIN) 03 Kepahiang. The method used in this study is a qualitative method with a descriptive approach. Data was obtained and collected through interviews and observations. The data analysis technique used to obtain valid data uses data reduction (summarizing), data presentation (a collection of information), and concluding (whole description). The conclusion obtained from this research is that the principal's role in improving teachers' professionalism at Madrasah Ibtidaiyah Negeri (MIN) 03 Kepahiang has a role as a manager, educator, motivator, and supervisor. Efforts made by school principals are to provide coaching and training such as professional teacher training (TPT), as well as assigning tasks according to expertise in their respective fields. The principal's efforts in improving teachers' professionalism are carried out to realize the goals, vision, and mission of education. The principal's role in increasing teacher professionalism uses participatory and situational leadership styles. Teachers can develop their abilities according to their respective competencies without being limited; there is the provision of coaching and training that will be followed by teachers at Madrasah Ibtidaiyah Negeri (MIN) 03 Kepahiang such as teacher